2016
DOI: 10.1080/15427528.2016.1171817
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity for Agro-Nutritional Traits in African Landraces of Vigna subterranean Germplasm

Abstract: Breeding African indigenous crops with increased nutritional value has recently been strongly advocated as a sustainable rural-based strategy of partially meeting the nutritional requirements of a large proportion of Africa's population. This approach requires information on the extent of genetic diversity among available genetic resources. Forty bambara groundnut (Vigna subterranean (L) Verdc) landraces of African origin were evaluated for agronomic attributes, protein, and grain mineral contents in a replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 37 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Despite its nutritional and agronomic benefits, it is a paradox that the Bambara groundnut is a native African crop that produces nearly all the entirely balanced food components, is easy to farm, and requires little soil, should be confined to its continent ( Doku, 1996 ) with no released variants. In Ghana, the Bambara groundnut is still cultivated as landraces without any genetic improvement with its associated low yields ( Adu-Dapaah et al., 2014 , Alake and Alake, 2016 ). Researchers have however identified many beneficial traits for improvements of the crop ( Basu et al., 2007 , Karikari, 2000 , Mwale et al., 2007 , Ntundu et al., 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite its nutritional and agronomic benefits, it is a paradox that the Bambara groundnut is a native African crop that produces nearly all the entirely balanced food components, is easy to farm, and requires little soil, should be confined to its continent ( Doku, 1996 ) with no released variants. In Ghana, the Bambara groundnut is still cultivated as landraces without any genetic improvement with its associated low yields ( Adu-Dapaah et al., 2014 , Alake and Alake, 2016 ). Researchers have however identified many beneficial traits for improvements of the crop ( Basu et al., 2007 , Karikari, 2000 , Mwale et al., 2007 , Ntundu et al., 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the emphasis is on S. stenocarpa agro-nutritional yield. The yield accumulations occur through pathways in food nutrient translocations from different sources during photosynthesis [17]. Either significant or otherwise, yield improvement strategy must identify the contributory role of other trait components to yield improvement.…”
Section: Introductionmentioning
confidence: 99%
“…It was documented by the scholars that there are significant variations of about 0.05 percent, and 0.01 percent is used to provide information on genotype performance across sources of variations in the literature. [17] considered significant variations of seed weight, plant biomass and pod filling time in Vigna subterranean, respectively. In addition, the outlined selection statistics were used to identify the contributory roles of traits to yield.…”
Section: Introductionmentioning
confidence: 99%
“…The PCA which indicated that only few eigenvalues explained the total genetic variation found in the population further confirmed that considerable genetic differences existed in the studied germplasm. Alake and Alake (2016) used a few eigenvalues to elucidate diversity among bambara groundnut landrace with nutritional and agronomic traits. The PC1 accounted for 49.04% of total variation with pod dry weight, yield, seed dry weight, petiole length, plant height, number of pods per plant, days to maturity and number of leaves having more loadings.…”
Section: Discussionmentioning
confidence: 99%